Design of a generic method for single dual-tracer PET imaging acquisition in clinical routine. (21st April 2023) - Taheri, Nasrin; Le Crom, Benjamin; Bouillot, Caroline; Chérel, Michel; Costes, Nicolas; Gouard, Sébastien; Marionneau-Lambot, Séverine; Merlin, Thibault; Visvikis, Dimitris; Stute, Simon; Carlier, Thomas
Abstract: Using different tracers in positron emission tomography (PET) imaging can bring complementary information on tumor heterogeneities. Ideally, PET images of different tracers should be acquired simultaneously to avoid the bias induced by movement and physiological changes between sequential acquisitions. Previous studies have demonstrated the feasibility of recovering separated PET signals or parameters of two or more tracers injected (quasi-)simultaneously in a single acquisition. In this study, a generic framework in the context of dual-tracer PET acquisition is proposed where no strong kinetic assumptions nor specific tuning of parameters are required. The performances of the framework were assessed through simulations involving the combination of [ 18 F]FCH and [ 18 F]FDG injections, two protocols (90 and 60 min acquisition durations) and various activity ratios between the two injections. Preclinical experiments with the same radiotracers were also conducted. Results demonstrate the ability of the method both to extract separated arterial input functions (AIF) from noisy image-derived input function and to separate the dynamic signals and further estimate kinetic parameters. The compromise between bias and variance associated with the estimation of net influx rate K i shows that it is preferable to use the second injected radiotracer with twice the activity of the first for both 90 min [ 18 F]FCH+[ 18 F]FDG and 60 min [ 18 F]FDG+[ 18 F]FCH protocols. In these optimal settings, the weighted mean-squared-error of the estimated AIF was always less than 7%. The K i bias was similar to the one of single-tracer acquisitions; below 5%. Compared to single-tracer results, the variance of K i was twice more for 90 min dual-tracer scenario and four times more for the 60 min scenario. The generic design of the method makes it easy to use for other pairs of radiotracers and even for more than two tracers. The absence of strong kinetic assumptions and tuning parameters makes it suitable for a possible use in clinical routine.